Kontestasi Pemasaran Kopi Gayo di Aceh Tengah dan Bener Meriah - M Nazaruddin; Abdullah Akhyar Nasution; Ade Ikhsan Kamil; Putri Prastika (Department of Anthropology, 2022)
Abtract: The emergence of classification and orientation of coffee farmers that focuses on preserving local values and aims solely for commercialization has created a marketing contest for processed coffee products in the Gayo highlands. Based on this, this study aims to identify how the contestation that occurs at the level of gayo coffee marketing along with the actors involved in it. That is, this article wants to explain the understanding and practice of contestation that occurs between coffee farmers with various farming practices with specialty coffee producers and export-based coffee producers. By using a qualitative method with a descriptive type, the researcher tries to understand (verstehen) so that the intensity of the interaction between the researcher and the subject emerges. So that efforts to capture meaning from the point of view and appreciation of coffee processing business actors on their motives and choices of actions in managing coffee agricultural products will be revealed. The results show that there are two main actors in the coffee marketing model in the Gayo highlands, namely cooperative-based farmer groups representing export market schemes and roasting companies representing regional and national market schemes.Abstrak: Munculnya klasifikasi dan orientasi petani kopi yang berfokus pada pelestarian nilai lokal serta bertujuan untuk komersialisasi semata telah memunculkan kontestasi pemasaran produk olahan kopi di dataran tinggi Gayo. Berdasarkan hal tersebut, studi ini bertujuan untuk mengidentifikasi bagaimana kontestasi yang terjadi di aras pemasaran kopi gayo beserta dengan aktor yang terlibat di dalamnya. Artinya, artikel ini ingin menjelaskan tentang pemahaman dan praktek kontestasi yang terjadi diantara para petani kopi dengan ragam praktik bertani dengan produsen kopi specialty dan produsen kopi berbasis ekspor. Dengan menggunakan metode kualitatif dengan tipe deskriptif, peneliti berusaha memahami (verstehen) sehingga muncul intensitas dari interaksi antara peneliti dengan subjek. Sehingga upaya menangkap makna dari sudut pandang dan penghayatan para pelaku usaha pengolahan kopi atas motif dan pilhan tindakan mereka dalam mengelola hasil pertanian kopi akan bisa diungkap. Hasil penelitian menunjukkan bahwa ada dua aktor utama dalam model pemasaran kopi di dataran tinggi Gayo yaitu kelompok petani berbasis koperasi yang mewakili skema pasar ekspor dan perusahaan roasting yang mewakili skema pasar regional dan nasional.